Workshops for editors in the central region of Cuba: a proposal for the improvement of scientific journals in medical sciences - Yurima Hernández de la Rosa; Mikhail Benet Rodríguez; Francisco Luis Moreno Martínez; Ana María Molina Gómez; Belkis González Aguiar; Lucitere Rodríguez González (Medisur)
An analysis on the importance of the development of publishing workshops developed in the center of the country with the participation of an important group of partners dedicated to this work in 15 scientific journals in the field of medical sciences of health in the region. The authors also address the issue of fraud in the scientific literature from a national to respect debate and the discussion developed on this important subject in the second workshop.